Elementy kultury materialnej i duchowej w poezji B. I. Antonycza. - Ksenicz, Andrzej (Acta Polono-Ruthenica, 2009)
The article is an attempt to elucidate certain elements in the poetry of B. I Antonycz, the author of Green Gospel, that is closely related to his biography. The material and spiritual cultural elements of the Lower Beskids residents, which were very important in Antonyczs poetry, are analyzed. These elements play a significant role in the projection of his small fatherland. In the authors poetic imagination, the memory of the green Beskids, rites, religiosity, beliefs and traditions of the mountaineers are transformed into an exceptionally colorful world, where the boundary between reality and myth is traversed.